The Influence Of Company Size, Financial Distress, KAP Reputation On Going Concern Audit Opinion Of Manufacturing Companies From BEI - I Made Wianto Putra; Putu Gede Wisnu Permana KAWISANA (International Journal of Environmental, Sustainability, and Social Science, 2020)
The company's financial condition can show that the company can last for a certain amount of time. Going concern audit opinion is defined as an opinion issued by the auditor based on an audit that has been conducted, in which there are doubts about the ability of a business in maintaining its continuity of life to continue its business as a business entity in the future. The purpose of this study is to empirically examine the Effect of Company Size, Financial Distress, and KAP Reputation on Going Concern Audit Opinions on Manufacturing Companies on the Indonesia Stock Exchange (BEI) in 2016-2018. Where the number of samples of this study was 31 companies with 3 years of observation with purposive sampling. Data collection was carried out in this study with the study of documentation through the company's annual financial report or annual report obtained from the website www.idx.co.id. The method in this research is logistic regression analysis. From the results of the study, it can be concluded that Company Size and Financial Distress have a negative effect on ongoing concern audit opinion and Public Accounting Firms' reputation has a not significant positive effect on ongoing concern audit opinion.